Digital Evidence Tracing in the Investigation of Identity Theft in the E-Commerce Era - Shinta Widhaningroem; Yeni Widowaty (Formosa Journal of Social Sciences (FJSS), 2024)
This research analyzes the application of regulations in prosecuting cyber crime in identity theft on e-commerce platforms in Indonesia. This study uses normative juridical research methods. This research considers various relevant laws, such as the Information and Electronic Transactions Law (UU ITE), the Criminal Code (KUHP), the Copyright Law, the Telecommunications Law, the Company Documents Law, and the Money Laundering Crime Law. Analysis shows that this law provides a strong legal basis for law enforcement to take action against cybercriminals and impose appropriate criminal sanctions. Apart from that, the law regulates electronic evidence, strengthening the investigation process against perpetrators. However, prosecuting cybercrime cases of identity theft on e-commerce platforms often experiences obstacles, especially in arresting suspects and confiscating evidence. This is due to the characteristics of digital crimes which are often complex and difficult to trace, as well as the lack of adequate capabilities and resources on the part of law enforcement in handling these types of cases. Greater efforts are needed to increase law enforcement capacity, as well as closer cooperation between authorities and e-commerce platform providers to increase the effectiveness of law enforcement in dealing with cybercrime